Assessment of torque and power in an internal combustion engine using partial mixtures of biodiesel - Reyes Campaña, Guillermo Gorky; Castillo Reyes, José Andrés; Escalante Quezada, Alex Xabier (Ingeniería Solidaria, 2016)
Introduction: This article is the result of the research “Assessment of torque and power in an internal combustion engine using partial mixtures of biodiesel at 2,800 masl (meters above sea level), according to the norm sae j1349 and inen rte 017”, conducted by the research group of the Faculty of Motor Vehicle Engineering of the International University of Ecuador (Quito), from May 1, 2014 to July 13, 2015. The research concluded biodiesel’s behavior at certain heights, specifically at 2,800 masl, using partial mixtures of biodiesel with Colombian and Ecuadorian nationally produced biodiesel. Methodology: The comparative mathematical analysis is described of biofuel samples in percentages of B5, B10 and B30, furnished by the company Lafabril, while taking into account environmental factors native of the country where the tests were being conducted. Results: The data produced in the lab was quantitatively substantiated with partial mixtures of biodiesel, and in such a way were obtained the curvatures of torque and power, as well as the emission of particulate matter. Discussion: Using the characteristics of local fuel and their respective partial mixtures of biofuel, a decrease of particulate matter and efficient values of torque and power in biofuel B30 were obtained, being this last one the most stable and regular, since it didn’t produce spikes in the obtained information.